Answer:
[tex]16x^{6} +56x^{3}y^{3} z^{4} +49y^{6} z^{8} \\[/tex]
Step-by-step explanation:
To solve this type of problems first need to review some laws of exponents:
When you are multiplying the same base, you need to add the exponents.
[tex]x^{2} +x^{8} = x^{2+8} = x^{10}[/tex]
When you are raising a base with power to another power, you should keep the base and multiply the exponents:
[tex](x^{2} y^{5})^3 = x^{2*3} y^{5*3} = x^{6} y^{15}[/tex]
Now for the expression [tex](4x^{3} + 7y^{3} z^{4} )^2[/tex]
Write the multiplying factors:
[tex](4x^{3} + 7y^{3} z^{4} )(4x^{3} + 7y^{3} z^{4} )[/tex]
Multiply the term [tex]4x^{3}[/tex]
[tex](4x^{3} + 7y^{3} z^{4} )(4x^{3} + 7y^{3} z^{4} ) = 16x^{3+3} + 28x^3y^{3} z^{4}[/tex]
Then multiply the term [tex]7y^{3}z^{4}[/tex]
[tex](4x^{3} + 7y^{3} z^{4} )(4x^{3} + 7y^{3} z^{4} ) = 16x^{3+3} + 28x^3y^{3} z^{4}\\\\+ 28x^3y^{3} z^{4} + 49y^{3+3} z^{4+4}[/tex]
Simplify the exponents:
[tex](4x^{3} + 7y^{3} z^{4} )(4x^{3} + 7y^{3} z^{4} ) = 16x^{6} + 28x^3y^{3} z^{4}\\\\+ 28x^3y^{3} z^{4} + 49y^{6} z^{8}[/tex]
Add like terms:
[tex]= 16x^{6} + 56x^3y^{3} z^{4} + 49y^{6} z^{8}[/tex]